In-hospital Outcome of Use of Low Molecular Weight Heparin in Patients Undergoing Percutaneous Coronary Intervention - Chowdhury, Tariq Ahmed; Aziz, Mustafizul; Alam, Iftekhar; Zaher, Abuduz; Haque, Sayed Azizul; Chowdhury, Abdul Wadud (Bangladesh Heart Journal, 2018)
This prospective observational study was carried out in the Department of Cardiology of national institute of cardiovascular diseases (NICVD), Dhaka to assess the safety of low molecular weight heparin (LMWH) in patients undergoing percutaneous coronary intervention (PCI). Safety of low molecular weight heparin in comparison to unfractionated heparin (UFH) was observed in this study. In total data from 100 patients undergoing elective PCI was evaluated. Among them 50 patients in group I received I mg/kg intra-arterial LMWH and rest in group II received UFH. Demographic profile of individuals in both groups was almost similar. There was no significant difference in major coronary risk factors between the two groups. Patients were monitored during their stay in hospital for any complications like bleeding, haematoma, myocardial infraction and death. No death was observed in any group. Minor bleeding in group I and II (6% vs 105), Major bleeding (2% vs4%) and haematoma (6% vs 10%). Myocardial infraction no incidence in group I and 4% in group II. So complications was more prevalent in group II who were treated with UFH, but those were not statistically significant. The intra-arterial administration of LMWH in patients undergoing PCI is safe. The risk of acute and sub-acute coronary events and bleeding complications are similar in both groups and in hospital outcome there is less complication with LMWH used during PCI. Bangladesh Heart Journal 2018; 33(1) : 22-27